2020
DOI: 10.48550/arxiv.2012.11533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monotone RLC Circuits

Thomas Chaffey,
Rodolphe Sepulchre

Abstract: Maximal monotonicity is explored as a generalization of the linear theory of passivity, which allows for algorithmic system analysis of an important physical property. The theory is developed for nonlinear 1-port circuits, modelled as port interconnections of the four fundamental elements: resistors, capacitors, inductors and memristors. An algorithm for computing the steady state periodic behavior of such a circuit is presented.The research leading to these results has received funding from the European Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Here, both A and B are maximal monotone operators. Since, H is a strictly passive operator, H −1 is maximal monotone, by the argument similar to the passivity theorem in [14], [9] and fact that maximal monotonicity is preserved by relational inversion. The main observation from ( 2) is that the mixed-feedback structure translates into the difference of two maximal monotone operators.…”
Section: Problem Formulationmentioning
confidence: 87%
See 4 more Smart Citations
“…Here, both A and B are maximal monotone operators. Since, H is a strictly passive operator, H −1 is maximal monotone, by the argument similar to the passivity theorem in [14], [9] and fact that maximal monotonicity is preserved by relational inversion. The main observation from ( 2) is that the mixed-feedback structure translates into the difference of two maximal monotone operators.…”
Section: Problem Formulationmentioning
confidence: 87%
“…Early connections between maximal monotonicity and passive LTI systems is found in the literature on nonsmooth dynamical systems [20], [21], and fixed point methods are used to compute periodic solutions in nonsmooth Lur'e systems [22]. Recently, In [9], it is shown that the periodic outputs of periodically forced maximal monotone input-output operators, built from port connections of basic circuit elements, can be computed using fixed point methods. The main idea of [9] is as follows.…”
Section: Algorithmic Analysis Of Monotone Feedback Systemsmentioning
confidence: 99%
See 3 more Smart Citations